Body weight, weight change and hypertension in former top-level female swimmers - Haljaste, K.; Pihl, E. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Health behaviour of former top athletes has not been studied extensively. Fogelholm et al. (1994) showed that former athletes had healthier lifestyle as compared to sedentary controls. Previous participation in top-level sports decreases prevalence of cardiovascular risk factors only in those subjects who maintain physically active lifestyle (Pihl et al. 1998). The present study evaluates health habits, overweight and hypertension of former top-level female swimmers to establish whether they differed from similar characteristics of the controls. METHODS Cross-sectional study was performed in 32 former 35-69-years-old top-level Estonian female swimmers and 38 female controls. The swimmers and controls were comparable in age and occupation. The anthropometric data, and health parameters (general health status, diseases, blood pressure, smoking, alcohol consumption, musculoskeletal symptoms) as well as previous and current physical activity (PA) were estimated using a questionnaire by Sarna et al. (1993). RESULTS The results of the questionnaire showed that 37,5 % of the female ex-swimmers and 26,3 % of controls stayed physically active during the current period. No statistically significant differences were found in smoking habits, alcohol consumption, dietary habits as well as in mean blood pressure between the physically active and sedentary group. There were 4 and 5 hypertensive (³140/90 mmHg) subjects among ex-athletes and controls, respectively. In swimmers, BMI was significantly related with age (r=.386) In controls, BMI associated with hypertension (r=.644). Weight change was associated with hypertension (r=.478) and this relationship was stronger in controls (r=.533). No significant associations were found in PA and hypertension between the groups. DISCUSSION Our study revealed that no statistically significant differences were found in lifestyle patterns, weight increase and hypertension between the ex-swimmers and controls. Correlation analysis showed significant associations between BMI, weight change and hypertension in all subjects. In conclusion, overweight values have significant relationships with hypertension.